FUNGSI YUDISIAL UNTUK MENJAGA KEMANDIRIAN HAKIM DALAM SISTEM PERADILAN PIDANA - Kraisus Sitanggang (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Indonesia is a state law that has been declared in the constitution, as a country that upholds the law, will be established justice agencies to resolve those cases that occur in the community, one of them is the court, the court is part of the criminal justice system, where the court is the place to examine the case, which the judge who became breaker guilty or not a person, as law enforcement, judges should be is independent in deciding a case, where the decision was not impartial and free from political influence and power, and free from bribes though, that the independence of judges independent and impartial influence, it needs to be maintained and protected, the reality in the Indonesian constitution in the constitution in 1945 through an amendment, it has been maintained and is watching her body established the Commission on judicial and law on judicial power, its purpose is enable the independence and freedom of judges in deciding a case, in order to obtain a legal justice, which is guaranteeing protection of the rights of justice seekers and that is where it is said that Indonesia is a country of law.